Female sexuality, marriage and divorce in the fiction of Thomas Hardy, with special reference to the period 1887-1896 - Boumelha, P; Penny Boumelha (1981)
﻿ The thesis sets out to examine Hardy's representations of women in sexual and marital relationships, and to relate those representations to contemporary developments in sexual ideology and in fiction. An Introduction considers the way in which ideology exerts pressure upon literary form, and discusses the particular appeal of female characters to Hardy's imagination. The first chapter is concerned with the constitution of sexuality as a subject of public discussion, and with its decisive shift from the area of moral discourse to that of the scientific. The influence of Darwinism and of neo-Darwinism upon ideologies of sexual difference and the nature of woman is discussed, together with the ambiguous political status of much contemporary feminist thought. There follows a chapter on Hardy's experimentalism with genre and narrative voice in his early fiction, and its relation to his female characters. An examination of The Return of the Native situates it as Hardy's first attempt at a double tragedy, of a man and of a woman, intellectual and sexual. "Women and the New Fiction 1880-1900" gives an account of the development of the "Fiction of Sex" and the novel of the "New Woman", and discusses the novel of womanliness, liberal feminist fiction, and the fiction of womanhood. The challenge that these new forms and modes of writing posed to the dominance of realism in the period is discussed. The last three chapters examine Hardy's last major novels in this enabling context of the New Fiction, and focus on the experiments with narrative method that bring about a radical break between Tess of the d'Urbervilles and Jude the Obscure. A brief conclusion argues that Hardy's experimentalism must be seen in its relation to contemporary fictional practice, and not as the product of personal temperament or of his own sexual and marital experiences. The thesis ends with a bibliography of works consulted.